Advances in drug therapies for cytomegalovirus in transplantation: a focus on maribavir and letermovir. (2nd October 2020) - Bruminhent, Jackrapong; Razonable, R.R.
ABSTRACT: Introduction: Cytomegalovirus (CMV) challenges physicians who care for immunocompromised transplant recipients. Antiviral drugs are the cornerstone in the prevention and treatment of CMV disease, but they have toxicities that limit their effective clinical uses. Advances in antiviral therapeutics against CMV are needed. High antiviral efficacy, especially against drug-resistant CMV, and low risk of adverse toxicities are characteristics of an ideal drug for CMV infection. Areas covered: A comprehensive review of novel drugs was conducted to provide a concise summary of the latest advances in antiviral therapeutics for the management of CMV infection in transplantation. This review focuses on the clinical efficacy and safety of maribavir and letermovir. All studies related to maribavir and letermovir were identified through a search of PubMed, citation chasing, and the author's knowledge of the topic. Expert opinion: Maribavir and letermovir are the 'new kids on the block' in the antiviral drug management of CMV. Both drugs provide novel and unique mechanisms of antiviral activity that are distinct from the traditional polymerase inhibitors. Clinical trials of maribavir and letermovir are reviewed, and their (potential) roles in prevention and treatment algorithms are discussed. Finally, the integration of these novel antiviral therapies with immunologic strategies is emphasized.